2019
DOI: 10.1007/s12088-019-00833-x
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Role of ERG3 and Efg1 in Azoles-Resistant Strains of Candida albicans Isolated from Patients Diagnosed with Vulvovaginal Candidiasis

Abstract: Vulvovaginal candidiasis (VVC), caused by Candida albicans, affects women's health and life. We aimed to explore the correlation between ERG3 as well as Efg1 mutation/overexpression and azoles-resistance, and the correlation between ERG3 and Efg1 mRNA expression in C. albicans. First, C. albicans was isolated from clinical VVC patients. ERG3 and Efg1 mutations were detected by polymerase chain reaction (PCR) and sequencing, and the expression levels of these two genes were also identified by qRT-PCR. Correlati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Therefore, combination therapy, while reducing the overuse of drugs, may give a suitable approach for combating resistance against commonly used antifungals. Furthermore, the synergistic effect of Ag NPs and azoles (a class of antifungals) against FLZ nonresponsive C. albicans has been discussed by researchers [ 6 , 68 ]. In the present work, we also observed that Ag-Ni NPs work synergistically with FLZ and made FLZ nonresponsive C. albicans cells susceptible to FLZ treatment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, combination therapy, while reducing the overuse of drugs, may give a suitable approach for combating resistance against commonly used antifungals. Furthermore, the synergistic effect of Ag NPs and azoles (a class of antifungals) against FLZ nonresponsive C. albicans has been discussed by researchers [ 6 , 68 ]. In the present work, we also observed that Ag-Ni NPs work synergistically with FLZ and made FLZ nonresponsive C. albicans cells susceptible to FLZ treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Several metals, including silver, cobalt, nickel, and palladium, have been examined in the form of NPs. They have distinctive properties that have pushed their use in various applications [ 6 , 7 , 8 , 9 ]. Metallic nanoparticles have a wide range of biological, catalytic, and electrochemical applications [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, various multi-drug resistant, especially uconazole resistant C. albicans have been reported [9]. So, it is exigent to search for newer and more effective therapeutics [10]. In the last decade, much progress has been made in understanding the reasons responsible for antifungal resistance in C. albicans.…”
Section: Introductionmentioning
confidence: 99%
“…Previous study has implied that the drug resistance of C. albicans is a complex process involving multiple mechanisms 18,31 …”
Section: Discussionmentioning
confidence: 99%
“…Previous study has implied that the drug resistance of C. albicans is a complex process involving multiple mechanisms. 18 , 31 ERG11 has been proved to play an important role in drug resistance. We sequenced ERG11 gene in the all clinical strains, and found 17 kinds of synonymous mutations and 6 kinds of missense mutations.…”
Section: Discussionmentioning
confidence: 99%